A high-temperature superconducting energy conversion and storage system with large capacity. (September 2022) - Li, Chao; Li, Gengyao; Xin, Ying; Li, Wenxin; Yang, Tianhui; Li, Bin
Abstract: Due to the excellent performance in terms of current-carrying capability and mechanical strength, superconducting materials are favored in the field of energy storage. Generally, the superconducting magnetic energy storage system is connected to power electronic converters via thick current leads, where the complex control strategies are required and large joule heat loss is generated. In this paper, a high-temperature superconducting energy conversion and storage system with large capacity is proposed, which is capable of realizing efficiently storing and releasing electromagnetic energy without power electronic converters. The proposed system is based on the interesting interaction between multiple high temperature superconducting coils and the permanent magnet. The working principle and performance of the proposed energy conversion and storage system have been verified through both simulation and experimental tests. Its application prospect is promising in the field of railway transportation, electromagnetic catapult, and the superconducting magnetic energy storage. Highlights: A novel high-temperature superconducting energy conversion and storage system with large capacity is proposed. An analytical method has been proposed to explain its working mechanism. Factors that could affect working performance of the proposed system have been discussed. Experiments have been carried out to verify the validness of theoretical analysis and the proposed analytical method.